2016
DOI: 10.1111/rda.12701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca Ionophore On Blastocyst Production Following Intracytoplasmic Sperm Injection in Caprine Oocytes

Abstract: The aim of the present investigation was to study the effect of calcium ionophore activation on blastocyst production following intracytoplasmic sperm injection (ICSI) in in vitro-matured Caprine oocytes. A total of 470 in vitro-matured oocytes were selected and randomly divided in to three groups. Cumulus oocyte complexes (COCs) recovered by slicing the Caprine ovaries were matured in TCM199 supplemented with 10% foetal bovine serum (FBS) + 10% follicular fluid + FSH (5 μg/ml) + LH (10 μg/ml) + estradiol (1 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The future studies at our laboratory may decipher some of these questions in order to thoroughly elucidate the importance of FOLR1 as a pivotal biomarker suitable for prediction of augmented susceptibility of embryonic genomes to efficient epigenetic reprogramming of their transcriptional activities. The latter could enable the embryologists to estimate the increased developmental competences and molecular quality of caprine and other mammalian species embryos produced by such modern assisted reproductive technologies as microsurgical IVF by intracytoplasmic sperm injection (Kharche et al., 2016; Magata et al., 2019; Menéndez‐Blanco et al., 2020; Shirazi et al., 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al., 2021; Hernández Martínez et al., 2020; Samiec et al., 2019; Skrzyszowska & Samiec, 2020, 2021; Wiater et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tetraploid fertilized embryos production: Collection of ovaries, recovery of oocytes and in vitro maturation (IVM) was done as per the method of Kharche et al (2016). In vitro fertilization (IVF) was carried out as per the method described by Kharche et al (2011) with slight modifications.…”
mentioning
confidence: 99%
“…Collection of ovaries, recovery of oocytes and in vitro maturation (IVM) was done as per the method of Kharche et al (2016). Briefly, after 27 h of in vitro maturation, denuded oocytes were then chemically activated with 5 µM calcium ionophore for 5 to 7 min followed by 4 h culture in 2 mM DMAP.…”
mentioning
confidence: 99%